The diagnostic procedure for subjects with suspected pulmonary embolism. A recent comparison among the recommendations available from the international guidelines - Gualtiero Palareti (Bleeding, Thrombosis and Vascular Biology, 2024)
Acute pulmonary embolism (PE) is a common and potentially life-threatening disease characterized by the occlusion of arterial lung vasculature, typically due to thrombi traveling from a thrombotic vein in the lower limb. Several guidelines have been proposed worldwide to assist clinicians in its diagnosis, however, they are not consistent on the usage of diagnostic tools. This commentary reviews the literature and discusses the concordance/discordance between these international guidelines on PE diagnosis.